Knowledge, Awareness, and Practices of Nurses Regarding Occupational Musculoskeletal Disorders - Ita Marlita Sari; Tazkia Nazla Hudzaifa; Imelda Rosalyn Sianipar; Mukhlidah Hanun Siregar (Tirtayasa Medical Journal, 2026)
Musculoskeletal disorders (MSDs) are the second leading cause of non-fatal disability worldwide. This study assessed the relationship between nurse knowledge, awareness and practices regarding occupational diseases and the occurrence of MSDs at Banten Regional General Hospital, Indonesia. This study was an analytical observational study with a cross-sectional design that held from January to April 2024. A total of 134 nurses were selected through stratified random sampling. Eligible participants had ≥1 year of experience and completed validated questionnaires independently. Data were collected using the Nordic Body Map and a structured, reliable instrument adapted from previous studies. Associations between variables were analyzed using the Chi-square test. More than half of the respondents (53.7%) demonstrated insufficient knowledge, and 63.9% reported MSDs. Negative awareness were found in 61.2% of nurses, and 63.4% showed poor preventive practices. However, no significant associations were found between knowledge (p = 0.75), awareness (p = 0.55), or practices (p = 0.05) with MSD occurrence. Most nurses experienced MSDs, yet their awareness, and practices toward occupational diseases were not significantly related to these conditions. Regular ergonomic training and supervision are needed to enhance safe work practices and reduce the burden of musculoskeletal disorders among nurses.